Mining of ring-hydroxylating dioxygenase genes from PAH contaminated soil metagenome - Mohd Ashaari, Mardiana; Storey, Sean; Doyle, Evelyn (2015)
Bacteria tend to initiate PAH degradation by the action of multi-component aromatic ring dioxygenases which comprising a reductase, a ferredoxin and terminal ring-hydroxylating dioxygenase. The potential for PAH degradation by the ring-hydroxylating dioxygenases in a PAH contaminated soil was assessed using metagenomic approaches. A metagenomic library was constructed from PAH contaminated soil and dioxygenase gene activity was examined by function-based screening of the library. An agar plate assay resulted in 3 positive fosmid clones out of 18,048 clones screened. Sequence-based screening of the metagenomic library was conducted by amplifying a ring hydoxylating gene (RHD) for both Gram positive and Gram negative bacteria. The RHD gene specific for Gram negative bacteria was amplified in 14 fosmid clones but none of the clones tested positive for the gene associated with Gram positive bacteria. Although not detected in the metagenomic library, high levels (≈300,000 copies per ng DNA extracted) and expression (82,704 copies per ng cDNA) of the RHD gene from Gram positive bacteria were detected in the contaminated soil using quantitative PCR. In addition, metatranscriptomic analysis confirmed the expression of RHD gene for Gram positive bacteria which could be mapped to a phenanthrene degradation pathway. This study provides deeper understanding on the ring-hydroxylating dioxygenases involved in PAH biodegradation. This information may be useful in the development of bioremediation strategies through bioengineering of these enzymes.